Effect of light supply in photobioreactors on the biomass productivity and energy efficiency of Scenedesmus sp - Gani, Aliya Habibti (Centre for Bioprocess Engineering Research, 2015)
Production of biofuel from microalgae is an attractive and sustainable option for meeting rising global energy demands and mitigating global warming. However, for commercial production of microalgae to be economically feasible, high biomass productivities and low auxiliary energy inputs must be achieved in large photobioreactors. According to literature, one of the main factors limiting growth is the inefficiency of light utilization (Posten, 2009; Janssen et al., 2003; Carvalho et al., 2006). In a photobioreactor, as biomass concentration and depth of culture increase, the amount of light that is able to penetrate the culture decreases exponentially. This occurs because of mutual shading of algal cells via adsorption of pigments or via scattering of cells. The purpose of this study was to optimize biomass productivity and biomass concentration by developing a thorough understanding of the microalgal response to light. In particular, the effects of light source, light intensity, configuration (internal and external), reactor design and the related variation in light/dark cycling were investigated.